Outcome Evaluation of Participation Learning Program in Prehypertension Group: Phichit Hospital - Theerakarunwong, Sunee (Journal of Health Science of Thailand, 2018)
This one-group pre test - post test study assessed outcomes of application of participation learning program to 116 prehypertensive Amphoe Mueang Phichit patients. It was shown that high risk factors for hypertension were, such as, higher BMI, waist size, and family history of diabetes mellitus and cardiovascular disease. Comparative results before and after using participation learning program follow up for 1 year that showed significantly statistical differences (p < 0.05) in all of participantsี knowledge of the risk factors, severity of hypertension, level of knowledge, personnel support for stimulation to preventing hypertension, level of knowledge about benefits and obstacles of hypertension prevention except receiving information about hypertension. This study showed a significant statistical difference (p <.05) in diet modification and physical activity. It is expected that this group will be able to prevent hypertension in the future as no hypertension could be detected further among them in a-year follow up.